The Improving Students’ Vocabularies Using Newspapers as an Authentic Materials - Zahwa Azwaza Kalima'aza; I Putu Sukmaantara; Wiwiek Eko Bindarti (English Education Study Program, 2021)
Authentic material is the material that the contents and the language used is close to the students’ real life. Authentic materials have not been specifically produced for the purpose of language teaching and this easily differentiates it from textbook materials. In addition, the use of authentic materials is expected to bring students in direct contact with reality so that students are interested in the vocabulary learning process. This research aims to find out the use of the authentic materials; English newspapers in teaching vocabulary. The participants of this research are the eleventh grader of Muhammadiyah 2 Genteng Senior High School which consists of 31 students. The design of this research is classroom action research. There are two kinds of data collected by the researcher; primary and secondary data. The primary data were collected from the students’ observation, and vocabulary test, while the secondary data were collected from the result of interview, and documentation. In this research, the researcher found that in the first meeting, the students’ participation was 65% and in the second meeting was 84%. Moreover, the students’ vocabulary scores have improved from 61.29% to 87.097%. It can be concluded that the use of the authentic materials; English newspapers can improve the eleventh grade students’ vocabulary achievement. Keywords: Authentic Materials, Vocabulary, Newspapers